MODIFIKASI MESIN PENIRIS MINYAK DAN KELAYAKAN FINANSIAL PRODUKSI KERIPIK BAYAM - Ahmad Thoriq; Totok Herwanto; Drupadi Ciptaningtyas (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2018)
Spinach chips is one of the snack products with the main ingredients of fried spinach using flour. The quality of spinach chips is influenced by the amount of oil contained in spinach chips. The use of spinner machine is proven to reduce or eliminate the oil content quickly and improve the quality of the product but the spinner machine available on the market can not be used to drain the oil contained in spinach chips because the rotational speed in the setting of more than 400 rpm can cause damage to spinach chips . This study aims to modify the spinner by lowering the speed of rotation and do the financial feasibility analysis of spinach chips production. The method used in this research is through the approach of engineering design and financial feasibility. The design approach consists of problems identification, formulation of modification concept, functional and performance test while some parameters calculated in financial feasibility analysis are: cost of production (HPP), net present value (NPV), benefit cost ratio (BCR), internal rate of return (IRR), and payback period (PBP). The results showed a decrease in rotational speed from 532.50 rpm to 258.18 rpm was proven to be able to remove the oil content on spinach chips and avoid the damage of spinach chips from 50% to no broken spinach chips. At production capacity of spinach chips 150 kg / month obtained cost of production amounted to Rp. 43,087 / kg. When spinach chips sold at market price Rp.50,000 / kg obtained NPV of Rp. 15,088,782/ month, BCR of 1.10, IRR of 12% and capital will return in the eigth month.